Improving the Ability to Understand Mathematical Concepts Through Problem-Based Learning (PBL) and Manipulatives in Class V Students of MIN 2 Pariaman City - Husna, Fitriatul (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Many primary school students struggle with conceptual understanding in mathematics, particularly in areas such as fractions, decimals, and measurement, which impedes problem-solving and transfer. This Classroom Action Research (PTK) investigates whether a Problem-Based Learning (PBL) model reinforced with manipulatives and a small project task can improve the conceptual understanding of Grade V students at MIN 2 Kota Pariaman. The research employed two cycles of action: planning, action, observation, and reflection. Participants were 18 Grade V students. Instruments included an 18-item concept test (pre-test and post-tests), observation checklists, project rubrics, work samples, and semi-structured interviews. Quantitative data were analyzed descriptively (means, percent meeting KKTP) and, where appropriate, paired comparisons; qualitative data were analyzed thematically. Mean scores improved from 61.40 (pre-test) to 74.10 (post-test I) and 86.00 (post-test II). The percentage of students meeting the established Kriteria Ketercapaian Tujuan Pembelajaran (KKTP) rose from 39% to 67% and then to 94%. Qualitative data indicated enhanced modelling, argumentation, collaboration, and motivation.